Conception, Consequences and Design of Cool Climate Viticulture Training Systems - Richard Danko; Pavel Pavloušek; Magdalena Kapłan; Kamila E. Klimek (Agriculture)
In this review, the problems, challenges and opportunities of trellis design are dealt with in the conditions of cool climate viticulture influenced by climate changes. Viticulture in so-called cool climate regions faces a number of weather and climatic extremes that directly or indirectly damage the grapes and so the wine. A suitable option is to use the structural and technical implementation of vine trellises—training systems, canopy management, and pruning methods which can help the plant withstand various extremes. At the same time, it is essential to choose trellis design training systems that growers can maintain and that support the appropriate quality of the grapes. Viticultural regions of warmer climate are strengthening the shading potential of training systems. Even so, the central viticultural areas withstand highly variable extremes of previous vintages with numerous shortcomings in the shading potential of trellis design. Meanwhile, the cool climate regions tend to use a trellis design with a simple canopy and easy sunlight exposition to reach the maximum solar contribution.